Strategy Department of Transportation in Implementation Supervision and Control Over Cargo in Riau Province - Arif Rahman Hakim (Institut Pemerintahan Dalam Negeri (IPDN), 2019)
The focus of this research is to look the strategy Departmen of Transportation inimplementation supervision and control over cargo in Riau Province, the factors thatinfluence and determine the strategies used to implement supervision and control overcargo by Departement of Transportation in Riau Province. The research uses theoryby George Robert Terry related to the Supervision and Control and conduct a SWOTanalysis and litmus test to determine strategies. This research uses a qualitativemethod with a descriptive approach. In collecting data, researchers conductedobservations, interviews and collected documents on the strategy Department ofTransportation in implementation supervision and control over cargo in RiauProvince. The results showed that the implementation supervision and control overcargo by Department of Transportation Riau Province had not run optimally. Thedirect supervision and conrol but the availability of financial resources, facilities andinfrastructure, and competent human resources are not fully owned and takenseriously. The influencing factors consist of internal factors and external factors whichare then determined by the strategies that must be carried out to succeed based onSWOT analysis and litmus test to get very strategic issues, including: Increasinggovernment commitment in carrying out oversight and control of more cargo, Conductcoaching and prevention by conducting guidance on body shop work,, Improvefacilities and infrastructure for oversight and control of more cargo, Make a plan forneeds and accelerate the implementation of supervision and control of overload,Increase the capacity of the apparatus through training in the implementation ofoversight and control of more cargo, Optimizing law enforcement for business actorsor drivers of vehicles that carry vehicles beyond the cargo limit.